2011
DOI: 10.1142/s2010324711000069
|View full text |Cite
|
Sign up to set email alerts
|

Interface Magnetism in Ferromagnetic Metal–compound Semiconductor Hybrid Structures

Abstract: Interfaces between dissimilar materials present a wide range of fascinating physical phenomena. When a nanoscale thin-film of a ferromagnetic metal is deposited in intimate contact with a compound semiconductor, the properties of the interface exhibit a wealth of novel behavior, having immense potential for technological application, and being of great interest from the perspective of fundamental physics. This article presents a review of recent advances in the field of interface magnetism in (001)-oriented fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…there is a uniaxial magnetic easy axis which is parallel to one of the substrate <110> crystal axis. Similar uniaxial magnetic anisotropies are commonly observed in thin ferromagnetic films grown on III-V semiconductor substrates 23 24 . While the detailed mechanism is not fully established, it is known to originate from the reduced symmetry of the bonding at the interface.…”
Section: Discussionsupporting
confidence: 78%
“…there is a uniaxial magnetic easy axis which is parallel to one of the substrate <110> crystal axis. Similar uniaxial magnetic anisotropies are commonly observed in thin ferromagnetic films grown on III-V semiconductor substrates 23 24 . While the detailed mechanism is not fully established, it is known to originate from the reduced symmetry of the bonding at the interface.…”
Section: Discussionsupporting
confidence: 78%
“…For studies of magnetic anisotropy, systems can be designed with one dominant interface. 31,32 The Cu/Co/ Ir provides an analogous system with a single dominant interfacial contribution to AMR. To demonstrate this any contribution due to scattering at the Co/Cu interface or the current-shunting effect of the Cu seed-layer must be accounted for.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffractometry showed that the Galfenol film has a mosaic structure with grain sizes of ∼12 nm, and their crystallographic axes misorientation of ∼1.3 deg. It is well established that thin films of iron and iron-based alloys epitaxially grown on GaAs exhibit intrinsic cubic and substrate-induced in-plane uniaxial magnetic anisotropies [36][37][38][39]. In particular, in Galfenol films on (001)-GaAs substrates the uniaxial anisotropy axis emerges along the [110] direction [35,40].…”
Section: Experimental Details a Samplementioning
confidence: 99%